Phytochemical Study of Methanolic Extract of Ferula persica Willd. Inflorescence and its Antinociceptive Effect in Male Mice - Sima Nasri; Majid Ghorbani Nohooji; Gholam Reza Amin; Azamalsadat Sharifi; Masoumeh Borbor; Fereshteh Shamohamadi; Mana Moghadasi (Institue of Medicinal Plants, ACECR, 2018)
Background: Nowadays treatment and control of pain is still one of problematic cases and syntetic analgesic drugs have several side effects. Objective: The aim of this study is to investigate the antinociceptive effects and phytochemical analysis of Ferula persica with respect to side effects of chemical drugs. Methods: The extract of plant inflorescence was prepared by percolation method. HPLC was used for phytochemical studies. In order to nociception test, male mice were used in acetic acid, immersion and formalin test. Mice were divided into experimental, control and positive control groups (receiving morphine) in each test. Results: In phytochemical analysis, four flavonoids consist of Quercetin, Luteolin, Apigenin and Rutin were identified. In all 3 pain tests, the experimental group had a significant difference with control group (P<0.05), but there was no significant difference with morphine group (P>0.05).   Conclusion: Methanolic extract of Ferula persica has antinociceptive effects, probably due to its sesquiterpenes and flavonoids.